Neuromuscular diseases and Covid-19: Advices from scientific societies and early observations in Italy - Angelini, Corrado (Eur J Transl Myol, 2020)
The risk of a severe course of COVID-19 is increased in patients suffering with Neuromuscular disorders (NMD) due to the following comorbidities: muscular weakness of the chest and diaphragm, use of ventilator supports and/or presence of tracheostoma, weak airway clearance, cardiac involvement, rhabdomyolysis, comoribities, steroid and immunosuppressant treatments. NMD display varying levels of disability in people with the same diagnosis, thus it is difficult to give COVID-19 related general recommendations. Present advicess were designed for patients, caregivers, general neurologists and non-specialist medical providers. They address frequently asked questions and basic service requirements and are supported by a series of in-depth references. In this truly unprecedented situation, the clinical management of neuromuscular patients during the COVID-19 epidemics - taking into account the related difficulties (patients who have suspended ERT, difficulty in contacting the doctors, etc.) - we propose to use a telemedicine device, i.e. the AIGkit application (AIGkit app), promoted and developed in 2018 by Fabrizio Seidita on behalf of the Italian Glycogenosis Association (AIG). The app was born to allow patients with Pompe disease to receive as far as possible continuous monitoring of their health. The support of all colleagues of the Italian Association for Myology (AIM) should extend its use to all NMD patients and beyond.